Bulk Composition of Fast-Spreading Oceanic Crust: Insights from the Lower Cumulates of the East Pacific Rise and from Cocos–Nazca Rift Basalts, Hess Deep. (9th March 2021) - Deasy, R T; Wintsch, R P; Meyer, R
Abstract: Cores recovered by International Ocean Discovery Program Expedition 345 to the Hess Deep Rift (HDR) include lower crustal cumulates from the East Pacific Rise (EPR) and primitive basalts from the Cocos–Nazca Rift (CNR). This study presents major and trace element compositions of channel samples—the continuous strips of rock removed during core splitting—from this expedition. Consistently high Eu/Eu* anomalies (1·37–5·22) and strong correlations among major element oxides in samples of cumulates indicate that rock composition at the meter scale is controlled by the accumulation and segregation of plagioclase and olivine. However, constant Mg# (82·22 ± 0·66) among 13 samples through a ∼50 m interval suggests that this cumulus was host to percolating, replenishing melt(s). Modeling finds this rock composition to be in equilibrium with melts having Mg# = 58–61. This is identical to the mean value of EPR lavas (57·7 ± 6·2) and suggests that melt buffering by permeable crystal mush is a common and important process in controlling mid-ocean ridge basalt compositions at fast-spreading ocean centers. Analyses of the cumulates provide the most comprehensive composition of in situ, fast-spreading lower oceanic crust currently available. These are compiled with analyses of gabbros, dikes, and lavas from across the HDR to calculate the bulk composition of fast-spreading oceanic crust produced at the equatorial EPR. This bulk composition is strikingly similar to the composition of the primitive basalts from the CNR, and these compositions have nearly identical modeled fractional crystallization histories. Lower abundances of incompatible elements in the primitive basalt suggest that CNR magmatism is the result of the resumption of decompression melting in mantle that previously produced EPR crust. However, higher abundances of chalcophile elements in the CNR basalt point to a diversity of mantle melts that is not evident in calculations of the composition of bulk oceanic crust.